Favourite Winnie The Pooh Stories - Milne, A A (Egmont Children's Books Ltd, 1999)
Contains stories about Pooh Bear and Christopher Robin, and their friends in the Hundred Acre Wood.
Keywords: Juvenile literature-Fiction